125k views
1 vote
Factor completely: 2a2 + a − 28

A. (2a − 7)(a + 4)
B. (2a+7)(a-4)
C. (2a-4)(a+7)
D. Prime

User Cheryll
by
6.6k points

2 Answers

1 vote

Answer:

A. (2a - 7)(a + 4).

Explanation:

2a2 + a − 28

= 2a^2 + 8a - 7a - 28

= 2a(a + 4) - 7(a + 4)

The a + 4 is common so we have:

(2a - 7)(a + 4).

User Khaled Osman
by
6.1k points
2 votes

Answer:

A

Explanation:

2a^2 + a -28

Recall: ax^2 + bx + c

a*c = 2*28= 56

sum of factors= +8-7 = 1

multiply of factor= 8*7=56

2a^2 +8a -7a-28

(2a^2 + 8a) - (7a - 28)

2a(a +4) - 7(a + 4)

Therefore

(2a-7)(a+4)

User Octavio Garbarino
by
6.1k points